2019
DOI: 10.1111/jocs.14401
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial myxoma: Unusual presentation as a cystic tumor

Abstract: Myxomas are the most common cardiac tumors, benign, and usually located in the left atrium. Typically echocardiography reveals a solid tumor, whereas cystic myxomas are rare with only a few cases documented in the literature. We describe the case of a 63-year-old, female patient with an unusual presentation of a left atrial myxoma as a cystic tumor. K E Y W O R D Scardiac tumors, intracardiac cysts, myxoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(12 reference statements)
0
4
1
Order By: Relevance
“…We report a case of myxoma with rich blood supply in the left atrium. The CE of the anechoic region in the cardiac myxoma indicated that it had vascular properties, with pathology confirmation, which is different from the previous view that the anechoic region in the cardiac myxoma is the cystic degeneration of the tumor 3 …”
Section: Case Imagecontrasting
confidence: 77%
See 1 more Smart Citation
“…We report a case of myxoma with rich blood supply in the left atrium. The CE of the anechoic region in the cardiac myxoma indicated that it had vascular properties, with pathology confirmation, which is different from the previous view that the anechoic region in the cardiac myxoma is the cystic degeneration of the tumor 3 …”
Section: Case Imagecontrasting
confidence: 77%
“…The CE of the anechoic region in the cardiac myxoma indicated that it had vascular properties, with pathology confirmation, which is different from the previous view that the anechoic region in the cardiac myxoma is the cystic degeneration of the tumor. 3 Cardiac myxoma originates from the multipotent mesenchymal stem cells of the endocardium, with the ability to differentiate into endothelial cells and myocardial cells, 4 and the function of angiogenesis and the potential of high vascularization, which manifests as a hypervascular tumor and needs to be distinguished from cardiac malignancies.…”
Section: Case Imagementioning
confidence: 99%
“… 4 Among them, cystic myxomas are rare, with only a few cases documented in the literature. 3 , 5–7 Herein, we reported a particularly inimitable form of a cardiac cystic myxoma and its anatomical and physiological conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Primary cardiac tumours are a rare group of diseases 1 and sometimes have unexpected morphology. 2 , 3 Among cardiac tumours, a cardiac myxoma occasionally contains cysts, necrotic tissue, fibrosis, haemorrhage, or calcification. 4 Among them, cystic myxomas are rare, with only a few cases documented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, these tumors are solid, round, or polypoid in shape and attached to the interatrial septum, lacking a cystic structure. However, cystic myxomas are exceedingly rare (3)(4)(5)(6)(7)(8). Intracardiac blood cysts are another unusual cardiac tumor, mainly seen in fetuses or infants under six months of age and rarely reported in adults.…”
Section: Introductionmentioning
confidence: 99%